Primary Leiomyosarcoma of the Ovarian Vein: Case Report and Literature Review. (June 2017) - López-Ruiz, María Elena; Yébenes, Laura; Berjón, Alberto; Hardisson, David
Primary leiomyosarcoma arising from the ovarian vein is extremely rare, with only 10 cases reported in the literature. We report on a case of leiomyosarcoma of the left ovarian vein in a 67-year-old woman who presented with abdominal discomfort. Pelvic ultrasound revealed a large, solid, irregular mass in close relation to the left ovary. The patient subsequently underwent a total hysterectomy with bilateral salpingo-oophorectomy. Histologically, the tumor was composed of interlacing fascicles of spindle cells with abundant eosinophilic cytoplasm, hyperchromatic nuclei, and prominent nucleoli. Mitotic activity was high, with 24 mitoses in 10 high-power fields. Areas of necrosis and hemorrhage were present within the tumor. Immunohistochemically, the tumor cells showed diffuse immunoreactivity for vimentin, muscle-specific actin, desmin, and caldesmon. The patient received chemotherapy postoperatively but subsequently developed disseminated metastatic disease (lung, liver, iliac lymph nodes, and peritoneum). Primary leiomyosarcomas arising from the ovarian vein are aggressive neoplasms, and the prognosis correlates with stage.